REVIEW OF THE MONOGRAPH by S. ALIYEVA "RELATIONS BETWEEN AZERBAIJAN AND THE PEOPLES OF THE NORTHERN CAUCASUS (XIX-EARLY XX CENTURIES.)."- BAKU: TURHAN, 2015. - 456 p. - Ancabadze, Urij Dmitrievic (History, Archeology and Ethnography of the Caucasus, 2019)
The monograph of the prominent Azerbaijani historian Sevinj Aliyeva is devoted to various bilateral relations and contacts between Azerbaijan and the peoples of the North Caucasus for more than a century in the difficult period of their history of the XIX - early XX centuries. Considering the objective nature of contacts, the author exaggerated the importance of the ethno-cultural factor, but deeply showed the political component of interregional cooperation.
Keywords: Sevinj Aliyeva; North Caucasus; Azerbaijan; interregional contacts; politics; economy; culture.